La enseñanza, el aprendizaje y el conocimiento científico desde la perspectiva de futuros profesores de Ciencias Naturales - Guirado Ariza, Ana María (2022)
This article presents an investigation developed in the context of initial teacher training in Natural Sciences, from a qualitative perspective, with the aim of identifying social representations related to teaching, learning, and scientific knowledge, in order to analyze and compare them. We worked with two cohorts of teacher students in the subject of pedagogical training. An evocation and hierarchization technique and a technique with images were used to identify the representations. The results show different representations in each cohort, with some common characteristics in relation to the subjects and specific scientific knowledge. They also show the need to encourage instances of reflection to help train teachers capable of overcoming their own limitations and who are critical of their own task.